Joint forest management: A case study of village Kotekoppa in Uttar Kannada district of Karnataka - Gopal, K Kadekodi; Bhat, Prabhakar R; Ravichandranath, N H; Seema, Hegde (Bangalore, 2004)
This is a paper based on a field study to evaluate an on-going joint forest management project (JFM). The methodology of the evaluation is a straightforward cost-benefit analysis, while reference to other alternative methods is made in passing. Attempts are made to incorporate all the major views of the people of the village or the beneficiaries in the analysis. In doing so, an approach of "with and without" JFM in a social accounting framework has been adopted. The findings reveal that the project can yield some net benefits to the people of the village, but not without uncertainties or sensitiveness of outcomes.
Keywords: Joint Forest Management - Field Study